Transportation dynamic behaviour of structural break and consumer price index - Mhd. Ruslan, Siti Marsila; Mat Ghani, Gairuzazmi; Khalid, Haniza; Mokhtar, Kasypi (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
This paper studies the dynamic behaviour of transportation price in Peninsular Malaysia and Sabah from 2004 to 2015 using disaggregated monthly price data of consumer price index (CPI). For that, unit root tests and cointegration tests with structural breaks are incorporated. The findings indicated that (i) both Zivot and Andrews unit root test and Perron unit root test provided fairly similar results; most of the break points occurred in 2008, (ii) the variables cointegrate in the Johansen cointegration test which indicates that there is a long-run relationship and (iii) the Gregory and Hansen test also demonstrated some form of cointegration with structural break(s), especially in 2008. Overall, this study intends to match the structural break points with the comparable critical economic events.